'I felt more homely over there … ': analysing tourists' experience of Indianness at Bollywood Parks Dubai. Issue 15 (3rd August 2022) - Nanjangud, Apoorva; Reijnders, Stijn
ABSTRACT: In recent years, Bollywood has expanded into a global, trans-textual phenomenon, consumed by a large audience-base worldwide. Existing research has shown how Bollywood offers Indians – both home and abroad – a cinematic image of their homeland, fostering a sense of belonging. This paper focuses on the popularity of Bollywood's transmedia culture in an international setting. More, in particular, it offers an empirical exploration of the tourist experience of Bollywood Parks Dubai – the first and largest theme park dedicated to Bollywood. Based on a series of in-depth interviews with 18 participants and accompanied by participant observations, this paper shows how Indian tourists use this leisure zone far away from the Indian subcontinent as a platform to connect and celebrate larger notions of Indianness. In experiencing nation-pride in a playful manner beyond the national borders, ideas of contemporary Indianness are redefined in a cosmopolitan context. The paper concludes by critically examining these popular celebrations of nationalism.